M2 macrophage-derived exosomes suppress tumor intrinsic immunogenicity to confer immunotherapy resistance - Naisheng Zheng; Tingting Wang; Qin Luo; Yi Liu; Junyao Yang; Yunlan Zhou; Guohua Xie; Yanhui Ma; Xiangliang Yuan; Lisong Shen (OncoImmunology)
T-cell-based immune checkpoint blockade therapy (ICB) can be undermined by local immunosuppressive M2-like tumor-associated macrophages (TAMs). However, modulating macrophages has proved difficult as the molecular and functional features of M2-TAMs on tumor growth are still uncertain. Here we reported that immunosuppressive M2 macrophages render cancer cells resistant to CD8+ T-cell-dependent tumor-killing refractory ICB efficacy by secreting exosomes. Proteomics and functional studies revealed that M2 macrophage-derived exosome (M2-exo) transmitted apolipoprotein E (ApoE) to cancer cells conferring ICB resistance by downregulated MHC-I expression curbing tumor intrinsic immunogenicity. Mechanistically, M2 exosomal ApoE diminished the tumor-intrinsic ATPase activity of binding immunoglobulin protein (BiP) to decrease tumor MHC-I expression. Sensitizing ICB efficacy can be achieved by the administration of ApoE ligand, EZ-482, enhancing ATPase activity of BiP to boost tumor-intrinsic immunogenicity. Therefore, ApoE may serve as a predictor and a potential therapeutic target for ICB resistance in M2-TAMs-enriched cancer patients. Collectively, our findings signify that the exosome-mediated transfer of functional ApoE from M2 macrophages to the tumor cells confers ICB resistance. Our findings also provide a preclinical rationale for treating M2-enriched tumors with ApoE ligand, EZ-482, to restore sensitivity to ICB immunotherapy.